Mini titanium plates; hearkening the end of non-rigid cranial bone flap fixation - Junaid, Muhammad (Pak J Med Sci, 2017)
BACKGROUND AND OBJECTIVE: Craniotomy bone flaps should be replaced for both cosmetic and protective purposes. Different methods are available commercially. The aim of this study was to assess outcome of bone flap fixation using mini titanium plates and screws. METHODS: Between March, 2011 and March, 2014, 71 patients underwent cranial bone flap fixation with mini titanium plates and screws after craniotomy and excision of supratentorial lesions at Combined Military Hospital, Peshawar. There were 42 males and 30 females with a mean age of 40.07. All patients had supratentorial lesions. Intracranial lesion size ranged from 3 cm by 2 cm to 7 cm by 5 cm. The changes of local incision and general condition were observed. RESULTS: Subcutaneous effusion occurred in two patients. One patient developed a mild postoperative wound infection. CT scan showed good repositioning of the flap and edge to edge apposition at two weeks after operation. All the patients were followed up for 12 months post operatively. Skull had good appearance without any discharge and, local deformity or effusion. Repeat CT/MRI showed no subsidence or displacement of cranial flap or artifacts. CONCLUSION: Mini titanium plate and screw fixation of cranial flaps is a simple, cost effective and safe option for repositioning and immediate stability as compared to traditional sutures.